The Relationship Of Reflective Thinking Skills And Critical Thinking Skills In Science Problem Solving - Diki Rukmana; Andi Suhandi; Achmad Samsudin (STKIP Singkawang, 2025)
To be a good science teacher requires reflective thinking skills and critical thinking skills, both of which play an important role in scientific problem solving activities. Theoretically, there is a relationship between reflective thinking and critical skills, but empirical testing is needed. The aim of this research is to see the relationship between reflective thinking skills and critical thinking skills in the science problem solving activities. This research is included in correlational research, with a research population of prospective elementary school teacher students in semester 4 at Muhammadiyah University Prof. Dr. Hamka is taking a science education course. The research sample consisted of 48 students. Simple random sampling is used in the sampling technique. The data analysis technique uses the Spearman correlation test to test the relationship between the two variables and a simple linear regression test to predict the linear relationship between the two variables. Based on research findings, there is a significant relationship between reflective thinking skills and critical thinking skills in problem solving activities with a correlation value of 0.779 (very strong). Apart from that, there is also a linear relationship between these two variables so that the critical thinking skills score can be predicted using the regression equation Y = 82.485 + 1.144X.